(untitled) - Pathé, Michele (Cambridge, U.K., 2002)
A practical and comprehensive survival manual for victims of stalking and related crimes, Surviving Stalking offers sound, realistic and practical advice to victims and guidance through each stage of the criminal justice processes in America, Britain, and Australia.
Keywords: Nạn rình rập,Stalking,Stalking victims,Stalkers